2023
DOI: 10.3390/su15043585
|View full text |Cite
|
Sign up to set email alerts
|

Telepresence Robot with DRL Assisted Delay Compensation in IoT-Enabled Sustainable Healthcare Environment

Abstract: Telepresence robots have become popular during the COVID-19 era due to the quarantine measures and the requirement to interact less with other humans. Telepresence robots are helpful in different scenarios, such as healthcare, academia, or the exploration of certain unreachable territories. IoT provides a sensor-based environment wherein robots acquire more precise information about their surroundings. Remote telepresence robots are enabled with more efficient data from IoT sensors, which helps them to compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…F Naseer [67] The deep reinforcement learning (DRL)-based deep deterministic policy gradient (DDPG) enhances control over the TR in case of connectivity issues. It also suggests a proper approach to maneuver the TR in unknown scenarios.…”
Section: Approaches Limitationsmentioning
confidence: 99%
“…F Naseer [67] The deep reinforcement learning (DRL)-based deep deterministic policy gradient (DDPG) enhances control over the TR in case of connectivity issues. It also suggests a proper approach to maneuver the TR in unknown scenarios.…”
Section: Approaches Limitationsmentioning
confidence: 99%
“…Several studies have identified essential considerations around usability, navigation, and control interfaces that broadly influence the acceptance and adoption of telepresence robots (11)(12)(13)(14), which can inform device optimization in exercise contexts. Smooth maneuverability and camera operations impacted the perceived ease of use and the intention to employ healthcare telepresence robots (15).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A primary concern with robots controlled via web‐based platforms is their dependency on communication networks, which exposes them to significant security risks [1–6], including unauthorised access, data breaches and hacking [7]. Another critical aspect is ensuring a user‐centred interface for seamless interactions between users and remote‐controlled robots.…”
Section: Introductionmentioning
confidence: 99%
“…A primary concern with robots controlled via web-based platforms is their dependency on communication networks, which exposes them to significant security risks [1][2][3][4][5][6], including unauthorised access, data breaches and hacking [7].…”
Section: Introductionmentioning
confidence: 99%